Enslaved daughters colonialism, law and women's rights - Sudhir Chandra, 1941- (New Delhi ; Oxford : Oxford University Press, 2008)
Adopting a radical-feminist stance, this book discusses the case of Dadaji Bhikaji against his 22 year-old wife Rukhmabai, filed when, after 11 years, she refused to live with him as per the Hindu marriage law. The book examines the lawsuit, looks at the role of the British during the court proceedings, and highlights some details of Rukhmabai's life that could reveal some psycho-social factors that gave her the strength to rebel.
Previous ed.: 1998.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Women -- India -- Social conditions; Women -- India -- History -- 19th century; Women -- Legal status, laws, etc. -- India -- History -- 19th century